Control Strategy and Optimal Configuration of Active-Support-Grid Type Decentralized Energy Storage System for Wind Farms - Cheng LI; Jie ZHANG; Ke SHI; Minghua XUE; Bo FENG (Zhongguo dianli)
A decentralized energy storage system for renewable energy stations has the characteristics of small capacity, wide dispersion, flexible deployment, and convenient expansion, which reduces the hidden dangers of accidents caused by battery aggregation and avoids the problem of high land acquisition and supporting construction costs. It can not only ensure refined management for nodes but also achieve cluster control, helping renewable energy stations improve grid-related operation performance, reduce assessment costs, and improve power generation efficiency. First of all, based on the principle of "decentralized layout and centralized control", a decentralized energy storage cluster control strategy is proposed, which virtualizes the decentralized energy storage into a centralized energy storage form and reasonably distributes power instructions according to the state of charge and state of health of energy storage. Secondly, according to the grid interconnection requirements, a coordinated control strategy for wind-storage systems based on frequency modulation priority is designed. By referring to the detailed rules of Jiangsu Province, a decentralized energy storage configuration optimization model is proposed to actively support the grid. The calculation example shows that the allocation of a certain scale of the energy storage system can reduce the assessment cost and improve the grid-related operation performance.